Toxicity Test of Dengen fruit Ethanol Extract (Dillenia serrata Thunb.) Using the BSLT (Brine Shrimp Lethality Test) Method - Pratiwi, Andi Nurul Faika (Makassar Natural Product Journal (MNPJ), 2024)
Dengen (Dillenia serrata Thunb.) is a plant that has various benefits. One part of the plant studied is dengen fruit. The toxic potential of dengen fruit can be known through toxicity tests. This study aims to obtain data and information on the toxicity of the fruit using the BSLT (Brine Shrimp Lethality Test) method against Artemia salina Leach larvae. The extraction method used in this study was the maceration method using 96% ethanol solvent to produce a % yield of 34.96%. The phytochemical screening test for the ethanol extract of dengen fruit was in the form of a color test which showed that the dengen fruit sample contained triterpenoid, tannin, saponin and flavonoid compounds. The toxicity test of the ethanol extract of dengen fruit used 150 Artemia salina Leach larvae which were divided into 5 concentrations (100 ppm, 200 ppm, 300 ppm, 400 ppm and 500 ppm) and 1 comparison or control group (seawater). The extract was put into the vial and 10 larvae were added each into the vial for each concentration of the test solution and also the control, then the volume was made up to 10 ml. Observations were made by looking at the mortality of Artemia salina Leach larvae after 24 hours of treatment and then analyzing the data using probit analysis by calculating the LC50 value. The LC50 value of the ethanol extract of dengen fruit is 97.274 ppm and is included in the toxic category.